2023
DOI: 10.1088/1361-6498/acbda7
|View full text |Cite
|
Sign up to set email alerts
|

Effective doses and risks from medical diagnostic x-ray examinations for male and female patients from childhood to old age

Abstract: Consideration of risks from medical diagnostic X-ray examinations and their justification commonly rely on estimates of effective dose, although the quantity is actually a health-detriment-weighted summation of organ/tissue absorbed doses rather than a measure of risk. In its 2007 Recommendations, the International Commission on Radiological Protection (ICRP) defines effective dose in relation to a nominal value of stochastic detriment following low-level exposure of 5.7 x 10-2 Sv-1, as an average over both se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
12
0
3
Order By: Relevance
“…It is essential to recall that, in order to construct the nominal risk coefficients and radiological detriment, the ICRP uses and aggregates data relating to persons with diverse characteristics (sex, age, two regions), such that the individual to whom the LNT model is applied is in fact a fictitious subject, averaged between a male and a female, exposed at all ages of their life, and both Asian and American-European (Harrison et al 2023). It is therefore irrelevant to try to demonstrate the accuracy of the LNT model in radiological protection, which remains fundamentally a mathematical construction, which cannot be compared to experimental or epidemiological results, but which integrates them.…”
Section: Usefulness Of the Lnt Model In The System Of Radiological Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential to recall that, in order to construct the nominal risk coefficients and radiological detriment, the ICRP uses and aggregates data relating to persons with diverse characteristics (sex, age, two regions), such that the individual to whom the LNT model is applied is in fact a fictitious subject, averaged between a male and a female, exposed at all ages of their life, and both Asian and American-European (Harrison et al 2023). It is therefore irrelevant to try to demonstrate the accuracy of the LNT model in radiological protection, which remains fundamentally a mathematical construction, which cannot be compared to experimental or epidemiological results, but which integrates them.…”
Section: Usefulness Of the Lnt Model In The System Of Radiological Pr...mentioning
confidence: 99%
“…In particular, this aggregated approach is one of the reasons why it is not recommended to use the nominal risk coefficients to perform risk assessments for specific individuals or categories of individuals (Harrison et al 2023). Even more so this statement is applicable to the use of the radiological detriment.…”
Section: Usefulness Of the Lnt Model In The System Of Radiological Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the International Commission on Radiological Protection (ICRP) publication 103, the lung, breast, and stomach are identified as the most radiosensitive organs, with the highest tissue weighting factor of 0.12 [5]. Studies have shown that these organs receive high organ doses during the posteroanterior (PA) projection of chest examination [6][7][8]. These concerns underscore the importance of prioritising patient protection during chest x-ray examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the highest age bracket of 75-84 years, where the LACMR value was 0.3 both for males and females, the values for 55-74 years are not lower by orders of magnitude, and thus one cannot ignore risks in this age group. Another recent paper [11] compared lifetime cancer incidence risks per Sv effective dose and showed that overall risks are higher by about a factor of two to three for the youngest age-at-exposure group, 0-9 years, than for 30-39 years adults, and lower by a similar factor for an age-at-exposure of 60-69 years. Thus, considerations of risk-benefits continue to be important even for those in higher ages.…”
mentioning
confidence: 99%